Islamic perspectives on instilling generic skills for students of higher learning institutions - Khalim Zainal,; Jamsari Alias,; Mohamad Mohsin Mohamad Said,; Wan Zulkifli Wan Hassan,; Aminudin Basir @ Ahmad,; Zulkifli Mohamad,; Norshidah Mohamad Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Generic skills can be defined as “core skills”,”key competencies”, ”underpinning skills” as well as “capabilities”. More recently, generic skills also include personal attributes that are linked with values and identity. The commonly accepted definition of generic skills is “those transferable skills which are essential for employability at some level for most” and the phrase “generic skills for employability” is now emerging as a common usage in public policy and research. This paper will discuss generic skills acquired by the students of one selected private university after they have undergone courses related in developing those skills. The findings from the research will be crossrelated to generic skills from the Islamic perspectives. This is in line with views from Islamic scholars such as Imam as-Shafi’i whom had proposed that interpersonal skills will develop generic skills that could inculcate a holistic individual comprising of Self Concept and Personality, Communication, Conflict resolution and Leadership. These skills are vital in carving human capital to be an important asset for an organization to achieve its goal. The paper will also discuss the findings and its relation from Islamic perspectives in fulfilling every individual’s attributes and values so as to be compatible with Islamic values.